2017
DOI: 10.1007/s11571-017-9448-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of spectral smearing of stimuli on the performance of auditory steady-state response-based brain–computer interface

Abstract: There have been few reports that investigated the effects of the degree and pattern of a spectral smearing of stimuli due to deteriorated hearing ability on the performance of auditory brain-computer interface (BCI) systems. In this study, we assumed that such spectral smearing of stimuli may affect the performance of an auditory steady-state response (ASSR)-based BCI system and performed subjective experiments using 10 normal-hearing subjects to verify this assumption. We constructed smearing-reflected stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
4

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 37 publications
1
6
0
4
Order By: Relevance
“…Second, we already verified the effect of variations in the smearing parameter of the simulator in a previous report, which showed that the auditory filter bandwidth of the simulator output widens as the value of the smearing parameter increases (Hwang et al 2015). To find the relevant values of the smearing parameter for each HI setup, we referred to a report of Glasberg and Moore (1986) that demonstrated that the equivalent rectangular bandwidth increased monotonically as the absolute threshold increased, as in our recent report (Hwang et al 2017). In the Glasberg study, the ratios of the equivalent rectangular bandwidth (ERBR) between HI and NH for a 1000 Hz pure-tone input signal were approximately 1.43, 2.31, and 3.18 for ML, MSL, and SL individuals, respectively.…”
Section: Synthesizing Spectral-smearing-reflected Stimulisupporting
confidence: 68%
See 4 more Smart Citations
“…Second, we already verified the effect of variations in the smearing parameter of the simulator in a previous report, which showed that the auditory filter bandwidth of the simulator output widens as the value of the smearing parameter increases (Hwang et al 2015). To find the relevant values of the smearing parameter for each HI setup, we referred to a report of Glasberg and Moore (1986) that demonstrated that the equivalent rectangular bandwidth increased monotonically as the absolute threshold increased, as in our recent report (Hwang et al 2017). In the Glasberg study, the ratios of the equivalent rectangular bandwidth (ERBR) between HI and NH for a 1000 Hz pure-tone input signal were approximately 1.43, 2.31, and 3.18 for ML, MSL, and SL individuals, respectively.…”
Section: Synthesizing Spectral-smearing-reflected Stimulisupporting
confidence: 68%
“…As we mentioned in the Introduction, the effect of the former is not serious in BCI applications because it can be avoided by selecting proper frequencies of auditory stimuli and adjusting the stimuli volume to a comfortable level for the individual; however, avoiding the effect of the latter is not a simple problem. As we demonstrated in our previous report, the degree and pattern of spectral smearing can affect the performance of an ASSR-based BCI system because they can affect the perception of the stimulus, the degree of concentration on the stimulus, and comfort in concentration (Hwang et al 2017). For this reason, to improve the clinical usability of the ASSR-based BCI system for persons with sensorineural HI, it is important to reflect the degree and pattern of spectral smearing of the individual in the parameter fine-tuning.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations